Prevention of Thrombus Growth by Antithrombin III-Dependent and Two Direct Thrombin Inhibitors in Rabbits: Implications for Antithrombotic Therapy - Brill-Edwards, Patrick; Van Ryn-McKenna, Joanne; Cai, Lu; Ofosu, Frederick A; Buchanan, Michael R (Thrombosis and Haemostasis, 1992)
We compared the abilities of heparin and two direct thrombin inhibitors to prevent fibrin accretion onto pre-existing thrombi in rabbits. Inhibition of thrombus growth was measured as the ability of each test compound to inhibit the accretion of 125I-fibrin onto thrombi pre-formed in jugular veins of rabbits. When administered as a continuous infusion, the two direct (i. e. antithrombin III-independent) thrombin inhibitors, r-hirudin and a tripeptide, Ac(D)-Phe-Pro-bor-Arg (P-8714) inhibited fibrin accretion as effectively as heparin, but did so in doses which generated little systemic anticoagulation, as compared to the marked anticoagulation associated with the heparin effect. However, both r-hirudin and P-8714 were more effective when they were administered as a single bolus injection than as a continuous infusion. Under the former conditions, there was only a transient systemic anticoagulant effect. We conclude that direct or antithrombin III-independent thrombin inhibitors are more effective than heparin in preventing thrombus growth. The limited effect of heparin is likely due to fibrin impairing the ability of heparin/antithrombin III to inactivate thrombin.